O impacto do foco regulatório na procrastinação e nas escolhas intertemporais - Kroth, Giana Lucca (2019)
Behavioral Economics is based on two pillars: (1) cognitive, responsible for the study of decisions under risk and uncertainty and the Prospects Theory; and (2) behavioral, focused on the study of intertemporal choices. The motivational Regulatory Focus Theory presented important results when related to the premises of the Prospects Theory, but has not yet been tested in relation to the intertemporal choices. Thus, the purpose of this thesis is to propose and apply a theoretical model that evaluates the impact of the Regulatory Focus on the temporal discount and procrastination. The proposed model verified the antecedent relation of the time discount to the procrastination (H1) and the hypotheses that both the promotion and the prevention focus are inversely related to the temporal discount (H2) and to the procrastination (H3), and the promotion focus, when compared to the prevention focus, presents higher rates in both constructs (H2 'and H3'). In order to apply the proposed model, it was necessary to adapt and validate the Pure Procrastination Scale (STEEL, 2010) and the Regulatory Focus Questionnaire (HIGGINS et al., 2001). In the adaptations, the translation, reverse translation, committee analysis and pre-test of the scales were carried out. For validation, the sample (n = 506) was randomly splited in three, in order to perform the steps of: Exploratory Factor Analysis (n = 163), Confirmatory Factor Analysis (n = 173) and External Confirmatory Analysis (n = 170), in which the correlation with correlated constructs was verified. For procrastination, it was not possible to identify a one-dimensional scale, but a three-dimensional scale: Decisional Procrastination, Behavioral Procrastination and Timeliness Procrastination. Regarding the regulatory focus, the structure of two uncorrelated factors - promotion and prevention - was validated. Monetary Choice Questionnarie (KIRBY; PETRY; BICKEL, 1999) was adapted to the Brazilian currency by converting the values according to the current exchange rate. To verify the hypotheses, the adapted and validated scales were applied (n = 607) and the model validated. Using the Structural Equation Modeling technique, it has been shown that, although low, the effects of regulatory focus and temporal discount on the facets of procrastination are both present and should be considered. The same can not be said of the effects of the regulatory focus on the temporary discount. The antecedent relation of the temporal discount with the procrastination has also been proven. The results indicated that promotion focus has a greater influence on the reduction of Decisional Procrastination, while prevention focus has a greater influence on the reduction of Behavioral Procrastination. Timeliness Procrastination did not present differences in the influence of the focus. As for the time discount rate, the results indicate that the greater the predominance of the promotion focus, the greater the discount rate. Finally, these results reinforce the multidimensional structure found for procrastination, since each dimension of procrastination responds differently to the effects of regulatory focus and also reaffirms the distinction between temporal discount and procrastination constructs, sometimes used as synonyms, but which present different effects from the individual’s chronic motivational referential.